Kepler ebook - Duchovny, David (Kepler., 2022)
David Duchovny's comic debut! When the Benadem, benevolent space gods, return to Kepler, a planet where homosapiens went extinct and all other hominid species thrived, their arrival threatens to plunge the world into chaos. West, a 16-year-old Neanderthal girl, is thrust into the conflict and her efforts—unique because of her mixed hominid heritage—not only change her life, but also reveal the merciless ambition and identity of the gods themselves. In the tradition of such canonical sci-fi classics as Planet of the Apes! Featuring art by acclaimed artist Phillip Sevy (Tomb Raider, Triage, The House).